Do we need a mechanism for solving sovereign debt crises? A rule-based discussion - Ugo Panizza (Graduate Institute of International and Development Studies, 2013)
This paper uses the rules of engineering as a rhetorical device to discuss why the international financial architecture needs a structured mechanism for dealing with sovereign insolvency. The paper suggests that the most important problem with the status-quo relates to delayed defaults and sketches a proposal aimed at mitigating this problem.
Keywords: F34; H63; 330; sovereign debt; sovereign default; Öffentliche Schulden; Länderrisiko; Finanzmarktregulierung; Internationaler Finanzmarkt; Weltwirtschaftsordnung; Welt